Smart parking for smart cities: a novel approach to reducing frivolous parking zone determination - Atiqur Rahman; Ali Md Liton (Institute of Advanced Engineering and Science, 2023)
Internet of things (IoT) infrastructures are rapidly expanding, which will lead to an unanticipated rise in demand for smart cities. The concept of a